China’s electric vehicles manufacturers’ expansion in the EU: patterns, barriers, and prospects - Аntonina A. Gomulina; Ilya A. Gorshkov (Научно-аналитический вестник Института Европы РАН)
The report examines the current situation regarding Chinese electric vehicle manufacturers entering the European market, including both investment and non-investment strategies used by these companies to expand abroad. The study identifies key partners from European countries who have facilitated the import of electric vehicles from China in recent years and summarizes the experience of direct investments by Chinese manufacturers and component suppliers in the European market. In this paper, we aim to systematically analyze the key barriers that hinder China’s entry into the European electric vehicle (EV) market. We examine customs, tariff, and administrative obstacles, as well as assess the potential for future growth of Chinese EV manufacturers in Europe. We consider factors such as the availability of critical raw materials and deepening cooperation between China and other BRICS countries. We have developed a simplified model that depicts China’s entrance into the European EV market at the expense of African resources. We posit that deepening collaboration between China and Africa, which is essential for supplying critical materials for EV production, will enhance China’s global dominance. This would also grant foreign manufacturers access to Chinese components, including batteries.